Development of Pre-Tensioning Device for CFRP Strips and Applicability to Repair of Cracked Steel Members. Issue 12 (December 2014) - Nakamura, H.; Yamamura, Y.; Ito, H.; Lin, F.; Maeda, K.
A method of repairing cracked steel members with pre-tensioned CFRP strips was investigated experimentally. Since a compressive force is introduced into the steel members by releasing the pre-tension in the CFRP strips after bonding, this technique is an effective fatigue crack repair method. With the aim of applying the method to a real structure, a simple, compact pre-tensioning device prototype was developed, and the effectiveness of the repair method was verified experimentally. The preliminary experiments were conducted using flat steel plates and varying the pre-tension of the CFRP strips. Results of tensile and creep tests revealed that it was possible to introduce a compressive force of approximately 36 kN into the steel plate rationally. Moreover, strain in the steel plate was measured for approximately 3 yrs. after introducing the compressive force, and a pre-stress loss of approximately 20% due to creep of the adhesive joint was observed under room-temperature conditions. Fatigue test results confirm that the application of this method to fatigue crack repair is feasible.